Using NDVI, climate data and machine learning to estimate yield in the Douro wine region - Barriguinha, André (2022)
The authors gratefully acknowledge: IVDP - Instituto dos Vinhos do Douro e do Porto, IP (Institute of Douro and Port Wines) (https://www.ivdp.pt/en), for providing historical data related to wine grape production for the entire DDR at the parish level; IPMA - Instituto Português do Mar e da Atmosfera, IP (Portuguese Institute for Sea and Atmosphere)